2020
DOI: 10.29252/ibj.24.4.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cerium Oxide Nanoparticles on Oxidative Stress Biomarkers in Rats’ Kidney, Lung, and Serum

Abstract: Background: The present study aimed to evaluate the effects of different concentrations of CONPs on the OS status in kidney, lung, and serum of rats. Methods: Male Wistar Rats were treated intraperitoneally with 15, 30, and 60 mg/kg/day of CONPs. The biochemical parameters, including TAC, TTG, MDA, SOD, and CAT were assayed in serum, kidney, and lung tissues. Results: MDA decreased, but TTG and CAT increased in serum by the administration of CONPs at 15 mg/kg. In kidney homogenate obtained from the group treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…There are many different studies that have con rmed the antioxidant properties of CeONPs in different tissues and in serum [39][40][41]. In a study by Kim et al in 2017, they showed under conditions similar to our experiment, that injection of the same amount of CeONPs could reduce the ROS levels at the lesion site after SCI.…”
Section: Discussionsupporting
confidence: 80%
“…There are many different studies that have con rmed the antioxidant properties of CeONPs in different tissues and in serum [39][40][41]. In a study by Kim et al in 2017, they showed under conditions similar to our experiment, that injection of the same amount of CeONPs could reduce the ROS levels at the lesion site after SCI.…”
Section: Discussionsupporting
confidence: 80%
“…Also, in this experiment, we measured the serum levels of malondialdehyde (MDA) and total antioxidant capacity (TAC) in 15‐day‐old neonates to assess the oxidative effect of CeO 2 . Experiments have been performed in this field, which have had contradictory results (Hamzeh et al, 2019; Sepanjnia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6: Effect of CeO2NPs treatment on TAC, TTG and MDA level in serum, kidney, and lung (Permission to reproduce was given by the Creative Commons Attribution License, (http://creativecommons.org/licenses/by/3.0/)which permits unrestricted use, distribution, and reproduction in any medium)[56] …”
mentioning
confidence: 99%